The Influence of Financial Inclusion and Macroeconomic on Foreign Direct Investment (FDI) Flows in The Organization of Islamic Cooperation (OIC) Countries - Farma Andiansyah (Universitas Ahmad Dahlan, 2021)
Foreign capital flows are important factors in the development of sustainable economies, especially in developing countries such as the OIC countries. Lately, the rapid development of the financial sector and macroeconomic stability became a serious concern by foreign investors, where financial inclusion and macroeconomics played an important role in attracting direct foreign capital flows (FDI). The study aims to investigate the role of financial inclusion and macroeconomic variables on the foreign direct flow of capital (FDI) by using data panels in 8 OKI member States during the 2012-2018 time span. The research uses the Fix Effect Model (FEM) Panel data Analysis tool, which is believed to be able to explain the correlation between independent variables and more accurate dependents. As for the results of the study showed that in partial only variable avaibility (the number of branches of the bank/100,000 adults) is a significant positive draws FDI in the OKI country. While on macroeconomic variables the exchange rates have significant negative effect on FDI, while interest rates and economic growth have significant positive relationships in attracting FDI.